Egyptian influences on Malaya's muslim kaum muda (young faction) before the second world war - Othman, Mohammad Redzuan (International Islamic University Malaysia, 2013)
The number of Malay students who had studied in Egypt shown a sharp increase since 1920’s. Despite facing many challenges and obstacles, the number of Malay students studied in Egypt increased since then rapidly. This article discusses the challenges and obstacles faced by Malay students studied in Egypt, especially at al-Azhar University, Cairo from 1910’s to 1950’s. Based on the library research, this study examines and analyzes the primary sources and secondary sources related to the challenges and obstacles faced by these students to further their studies in Egypt. This study also found that the departure of Malay students from Malaya to Cairo exposed them to a variety of challenges, either before embarking for the trip, or upon arriving in Egypt, particularly the process of obtaining their passport and visa. Despite of such challenges, the number of Malay students studied in Egypt continued increasing sharply since 1920’s, which proved that the Malay students, in spite of the challenges and obstacles faced continued to travel to Egypt in pursuit of religious knowledge at al-Azhar University, Cairo.